2014
DOI: 10.1016/j.ijsu.2014.10.031
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the use and implementation of checklists in surgical specialities – A systematic review

Abstract: The recent use of checklists in surgery has shown improvements in patient outcomes post-operatively. A review was conducted to establish the impact of the checklist on different surgical specialities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 28 publications
0
56
0
Order By: Relevance
“…However, hospitals that implemented the MSSCL well showed a greater reduction in maternal mortality than hospitals with poor implementation, which supports the argument that outcomes may be dependent on the quality of implementation. [16] To date only Haynes et al [4] have shown significant reductions in mortality, other studies having failed to do so. [2,[5][6][7][8] The overall complication rates in our study were lower than those reported by others.…”
Section: Other Findingsmentioning
confidence: 99%
“…However, hospitals that implemented the MSSCL well showed a greater reduction in maternal mortality than hospitals with poor implementation, which supports the argument that outcomes may be dependent on the quality of implementation. [16] To date only Haynes et al [4] have shown significant reductions in mortality, other studies having failed to do so. [2,[5][6][7][8] The overall complication rates in our study were lower than those reported by others.…”
Section: Other Findingsmentioning
confidence: 99%
“…In such a pressurised technological environment, safety is paramount in preventing errors. In addressing these concerns, within the perioperative setting Patel et al (2014) suggested that the World Health Organization Safety Checklist becomes a mandatory tool. In keeping with international best practice Ireland, too is committed to the provision of safe, high quality health services (HSE 2009).…”
Section: Introductionmentioning
confidence: 99%
“…(2)(3)(4)(5)(6) However, in contrast to studies that have found benefits to implementing a checklist, (1)(2)(3)(4)(5)(6) a study carried out in Ontario, Canada (21) on use of a checklist in 130 hospitals in an institutionalized format showed no significant improvement in mortality or surgical complications after three months of implementation. According to the authors, this finding could be partly attributed to the mandatory introduction of a checklist.…”
Section: Discussionmentioning
confidence: 99%
“…It also establishes the following as the program main objective: a set of demographic statistics for surgery that incorporate structural measures and results that track process effort, such as use of a safety checklist in the operating room. (1) The surgical safety checklist is considered a key element for reducing adverse events (1)(2)(3)(4)(5)(6) and aims to guarantee that surgical teams consistently follow critical safety measures to increase surgical procedure safety, reinforce accepted safety practices and promote better communication and work among the surgical team. However, the list proposed by the WHO is only a basic one.…”
Section: Introductionmentioning
confidence: 99%